The mediating role of self-esteem in the relationship between emotional creativity and wisdom in middle managers - Salek Moghadam, Somaye; Baghdasarians, Anita; Golshani, Fatemeh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: This study was conducted with the aim The mediating role of self-esteem in the relationship between emotional creativity and wisdom in middle managers. Methods: The cross-sectional research method is correlational and in order to respond to the research hypotheses, structural equation modeling analysis was used. The statistical population of this research was made up of all the middle level managers of private banks and Mahan Airlines in Tehran in first half 2021, from among them, 300 people were selected by staged cluster sampling method. In this research, the tools of wisdom (Ardelt, 2003), emotional creativity (Avril, 1999), and self-esteem (Rosenberg, 1965) were used, all of which are valid and had acceptable reliability. In order to analyze the data, SPSS-V19 and Lisrel-V8.8 software were used. Results: The findings of the research showed that the model has a good fit. The results showed that emotional creativity had a significant direct effect on wisdom. In connection with the existence of an indirect effect of emotional creativity on the wisdom of middle managers through self-esteem, it is confirmed with 95% confidence. Conclusion: Therefore, paying attention to the mentioned variables helps senior managers and researchers in choosing managers and designing more suitable for cultivating wisdom.